Case report: A pediatric case of Bickerstaff brainstem encephalitis after COVID-19 vaccination and Mycoplasma pneumoniae infection: Looking for the culprit - Monte, Gabriele; Pro, Stefano; Ursitti, Fabiana; Ferilli, Michela Ada Noris; Moavero, Romina; Papetti, Laura; Sforza, Giorgia; Bracaglia, Giorgia; Vigevano, Federico; Palma, Paolo; Valeriani, Massimiliano (Frontiers in Immunology, 2022)
Bickerstaff brainstem encephalitis (BBE) is a rare, immune-mediated disease characterized by the acute onset of external ophthalmoplegia, ataxia and consciousness disturbance. It has a complex multifactorial etiology and a preceding infectious illness is seen in the majority of cases. Immune-mediated neurological syndromes following COVID-19 vaccination have been increasingly described. Here we report the case of a child developing BBE two weeks after COVID-19 vaccination. Despite nerve conduction studies and CSF analysis were normal, BBE was diagnosed on clinical ground and immunotherapy was started early with a complete recovery. Later, diagnosis was confirmed by positive anti-GQ1b IgG in serum. Even if there was a close temporal relationship between disease onset and COVID-19 vaccination, our patient had also evidence of a recent Mycoplasma pneumoniae infection, that is associated with BBE. Indeed, the similarity between bacterial glycolipids and human myelin glycolipids, including gangliosides, could lead to an aberrantly immune activation against self-antigens (i.e. molecular mimicry). We considered the recent Mycoplasma pneumoniae infection a more plausible explanation of the disease onset. Our case report suggests that suspect cases of side effects related to COVID-19 vaccines need a careful evaluation in order to ruled out well-known associated factors before claiming for a causal relationship.